Diagnosis and management of breast implant capsule recurrence following mastectomy and subpectoral implant – innovative use of ADM for reconstruction. Issue 10 (10th October 2022) - Soh, Chien Lin; Asher, Christian M; Forouhi, Parto; Moyle, Penelope; Healy, Nuala Ann; Malata, Charles M
Abstract: It is well reported that patients who have undergone breast augmentation and subsequently develop breast cancer can successfully undergo breast-conserving therapy with preservation of their implants. However, there is a paucity of literature on the radiological investigations and surgical techniques in postmastectomy implant-reconstructed patients who develop recurrences to enable preservation of their implant-based reconstruction whilst effectively treating the local recurrence. The wide adoption of acellular dermal matrix use in prosthetic breast reconstruction in recent years has made radiological evaluation of such patients challenging. Herein presented is a case of a 37-year-old woman where wide local excision of a local recurrence abutting a peri-implant capsule following previous mastectomy and implant-acellular dermal matrix (ADM) reconstruction was performed with successful preservation of reconstruction volume (and shape) using an ADM patch to repair the capsular defect whilst retaining the implant in situ. Radiological investigation facilitated and guided the surgical planning and oncological clearance.